Aligning supply chain management and new product development: a theoretical framework. (24th August 2009) - Pero, Margherita; Sianesi, Andrea
Product features are defined by new product development (NPD) process so to fulfil clients' requirements. Supply chain performances are affected by product features. The magnitude of this effect is determined by supply chain decisions. In order to satisfy client's needs, in terms of new products, service level and costs, supply chain management (SCM) decisions should be aligned to product features, i.e., to the output of NPD process. Literature analysis shows that external and internal product variety and product novelty are the main product features to be considered to align SCM decisions to NPD. We developed a framework for NPD-SCM alignment assessment that takes into account all these relevant variables. NPD-SCM alignment is reached when the level of variety/innovation that is created during NPD and the variety/innovation that is/can be transported by the supply chain is equal to clients needs. A case study is presented to support the framework.